1999
DOI: 10.1016/s0009-9236(99)70065-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of terbinafine as a CYP2D6 inhibitor in vivo

Abstract: Terbinafine inhibits CYP2D6 sufficiently to produce a discordance between genotype and phenotype for the enzyme. The dextromethorphan/dextrorphan metabolite ratios increased in all individuals, with otherwise functional CYP2D6 activity. The disposition of CYP2D6 substrates coadministered with terbinafine may be significantly altered in extensive metabolizers for this cytochrome P450 isoform, who comprise approximately 93% of the population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 24 publications
3
62
1
1
Order By: Relevance
“…On the other hand, CYP2D6*10B, a gene copy with a C 188 pT mutation, is predominant in Chinese extensive metabolizers [6] and is associated with decreased CYP2D6 activity. We have found that the mean baseline MR values in the 10 Chinese EM subjects from the present study were about ®ve times as high as that in the six Caucasian EM subjects reported by Abdel-Rahman [2] (0.028t0.027 vs 0.006t0.003). Noticeably, there was no signi®cant difference in mean dextromethorphan MR values between the two groups after terbina®ne therapy (0.321t0.333 vs 0.282t0.076, P>0.05).…”
contrasting
confidence: 43%
See 1 more Smart Citation
“…On the other hand, CYP2D6*10B, a gene copy with a C 188 pT mutation, is predominant in Chinese extensive metabolizers [6] and is associated with decreased CYP2D6 activity. We have found that the mean baseline MR values in the 10 Chinese EM subjects from the present study were about ®ve times as high as that in the six Caucasian EM subjects reported by Abdel-Rahman [2] (0.028t0.027 vs 0.006t0.003). Noticeably, there was no signi®cant difference in mean dextromethorphan MR values between the two groups after terbina®ne therapy (0.321t0.333 vs 0.282t0.076, P>0.05).…”
contrasting
confidence: 43%
“…Four out of 10 EM subjects were converted to apparent PMs with respect to CYP2D6 ( Abdel-Rahman et al [2] showed that a mean 97-fold increase in the dextomethorphan MR was observed for six Caucasian extensive metabolizers after 2 weeks' treatment with terbena®ne. For 10 Chinese extensive metabolizers at the same daily dose as in our study the mean fold increase in dextromethorphan MR was six times less.…”
mentioning
confidence: 99%
“…The urinary concentrations of DM and its O-demethylated metabolite, DX, were determined using HPLC with fluorescence detection as described previously. 40 DM/DX ratios 40.3 were used to indicate a PM phenotype. In a single individual, a tramadol biodisposition profile was available in addition to a DM/DX ratio.…”
Section: Cyp2d6 Phenotypingmentioning
confidence: 99%
“…30 nM) and correspondingly marked reduction in the metabolism of the CYP2D6 substrate dextromethorphan in vivo. 60,64 Importantly, the activity of CYP2D6 may not return to normal for months after the completion of a prolonged course of therapy. 64 Clinically, terbinafi ne is demonstrated to interact with concurrently administered CYP2D6 substrates including amitriptyline, nortriptyline, desipramine, and venlafaxine.…”
Section: Clinical Pharmacology (Tables 1 and 2)mentioning
confidence: 99%